Modelování přenosu tepla pomocí diferenciálních rovnic - Sklenářová, Lenka (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2011)
Práce se zabývá základními principy přenosu tepla, odvozením parabolické rovnice vedení tepla jak v tyči, tak i ve vyšších dimenzí, včetně diskuse o okrajových a počátečních podmínkách. Řešením ustálených případů rovnic v daném prostředí, kde je významný pouze jeden směr.

The thesis focuses on basic principals of heat transfer, on deduction of parabolic equation, on heat conduction in a rod, as well as in higher dimension, including discussion on boundary and initial conditions. The thesis deals with solving steady states in given environment where only one direction is significant.
Modelling of the heat transfer by differential equations
Keywords: rovnice vedení tepla; stacionární případy; analýza LODRn; parciální diferenciální rovnice; heat equation; steady states; analysis of linear ordinary differential equation; partial differential equation